Case Report: Shared manifestation, distinct etiologies: severe pulmonary hypertension in both mother and neonate - Wang, Sihan; Yang, Ping; Xi, Hongmin; Yin, Xiangyun; Ma, Lili; Li, Liangliang; Li, Xianghong (Frontiers in Pediatrics, 2025)
BackgroundHereditary hemorrhagic telangiectasia (HHT) is a rare genetic disease. The prevalence of pulmonary arterial hypertension (PAH) in HHT patients is less than 1%. Severe pulmonary hypertension (PH) in pregnant woman due to HHT and reversible pulmonary hypertension in her neonate is even rarer.MethodsCases of mother and newborn with PH are presented, including their clinical manifestations, diagnosis, and treatment. Additionally, literatures were reviewed to explore the various causes of the disease.ResultsThe mother was diagnosed with HHT caused by an ACVRL1 gene variant, with her PH occurring as a complication of HHT type 2 (HHT2). The neonate was confirmed to be free of the ACVRL1 gene variant, and her PH resulted from impaired placental perfusion and adverse intrauterine environment secondary to severe maternal PH and anemia.ConclusionAttention should be paid to the progression of the disease and the comprehensive management strategies during pregnant HHT patient. Moreover, neonates born to HHT-affected mothers require evaluation for both HHT-related PH and reversible PH secondary to adverse intrauterine factors. This report aims to enhance the recognition of familial manifestations of HHT and raise awareness of the occurrence of postnatal PH in neonates of mothers with HHT, thereby facilitating early detection and timely intervention.